1978
DOI: 10.2466/pr0.1978.43.3f.1203
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in Evaluative Judgments against Foreign-Accented Job Candidates

Abstract: The purpose of this study was to determine the effects of the ethnicity of speakers, as suggested in accents, on judgments of suitability for a job, and to establish the relationship between listeners' attitudes and the evaluation of accented speech. 203 subjects acted as personnel consultants and evaluated 10 job applicants for four jobs varying in social status. Five candidates spoke with an English-Canadian and five with a foreign accent. Data showed discrimination in favour of English-Canadian and against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 6 publications
1
53
1
Order By: Relevance
“…And Davila, Bohara, and Sanz (1993) reported that stronger accents were associated with lower incomes among Mexican Americans. In a Canadian study by Kalin and Rayko (1978), listeners judged speakers with a general Canadian accent as more suited than non-native speakers to highstatus jobs. Sato's (1998) examination of attitudes toward L2 accent in Alberta revealed effects of location (rural vs. urban) and education level (high school vs. university) of the listeners.…”
Section: Les Attitudes Negatives Face Ala Prononciation Avec Accent Ementioning
confidence: 99%
“…And Davila, Bohara, and Sanz (1993) reported that stronger accents were associated with lower incomes among Mexican Americans. In a Canadian study by Kalin and Rayko (1978), listeners judged speakers with a general Canadian accent as more suited than non-native speakers to highstatus jobs. Sato's (1998) examination of attitudes toward L2 accent in Alberta revealed effects of location (rural vs. urban) and education level (high school vs. university) of the listeners.…”
Section: Les Attitudes Negatives Face Ala Prononciation Avec Accent Ementioning
confidence: 99%
“…The selective survey of research presented by Kalin and Rayko (1978) shows that a foreign accent plays an important role in communication -not only may it hinder mutual intelligibility, but it has also been shown to influence listeners' attitudes towards non-native speakers and may lead to discrimination. We consider it important to investigate what kind of judgements (e.g., intelligence, friendliness, reliability etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Another study addressing discrimination against foreign-accented speakers was conducted by Kalin and Rayko (1978) who investigated the effects of the speakers' ethnicity on judgements of suitability for a job. The participants in their study, who were English-Canadian speakers, acted as personnel consultants and evaluated ten job applicants (five with a Canadian accent, five with a foreign accent) for four jobs varying in social status.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, status was a composite measure that, in addition to perceptions of factors such as wealth and success, included ratings of perceived intelligence and education. In addition, evidence has indicated that individuals with a foreign accent may be discriminated against when they apply for high-status jobs (Kalin & Rayko, 1978).…”
mentioning
confidence: 99%